A case report of atypical teratoid/rhabdoid tumour in a 9-year-old girl - Chan, Kin Hup; Mohammed Haspani, Mohammed Saffari; Tan, Yew Chin; Kassim, Fauziah (Universiti Sains Malaysia, 2011)
Primary central nervous system atypical rhabdoid/teratoid tumour (ATRT) is a rare and highly malignant tumour that tends to occur in infancy and early childhood. The majority of tumours (approximately two-third) arise in the posterior fossa. The optimal treatment for ATRT remains unclear. Options of treatment include surgery, radiotherapy, and chemotherapy. Each of their role is still not clearly defined until now. The prognosis of the disease is generally unfavourable. This is a case report of ATRT in an atypical site in a 9-year-old girl.